The Regulation of Staphylococcus aureus-Induced Inflammatory Responses in Bovine Mammary Epithelial Cells - Cai, Mingcheng; Fan, Wenqiao; Li, Xiaoying; Sun, Hanchang; Dai, Liuliu; Lei, Defang; Dai, Ying; Liao, Yuhua (Frontiers in Veterinary Science, 2021)
Mastitis is an inflammatory disease mainly caused by microbial infection. Staphylococcus aureus (S.aureus), the major etiological microorganism, derived lipoteichoic acid (LTA) has been identified to activate inflammatory responses, but the regulatory mechanism of cellular or intercellular is unclear. This study was designed to evaluate the effects of LTA in bovine mammary epithelial cells (Mac-T), and elaborated the regulation of miRNAs. In this study, cells were infected with LTA for different times, the expression and concentration of TNF-α and IL-6 showed to be upregulated. Furthermore, LTA could be recognized by TLR2 and activate TLR2/MyD88 mediated PI3K/AKT pathway, and TLR2 plays a pivotal role in LTA induced inflammatory responses. Additionally, qRT-PCR was employed and the results showed that miRNA levels increased and reached the highest at 3h, and then gradually decreased over time in Mac-T cells. In exosomes, the levels of 11 miRNAs were up-regulated and 3 miRNAs were down-regulated at 24h. In addition, miR-23a showed the highest increase in Mac-T cells treated with LTA, and targets PI3K to regulate inflammatory responses. Subsequently, Mac-T cell derived exosomes were identified to play a cell-cell communication by promoting M1 polarization of bovine macrophages. In summary, our study demonstrated that LTA could activate inflammatory responses viaTLR2/MyD88/PI3K/AKT signaling pathway, and miR-23a inhibited it by targeting PI3K. Furthermore, we found that Mac-T cell-derived exosomes might be associated with the inflammatory responses by promoting M1 polarization of bovine macrophages.